Trichloroethylene decomposition by fenton reaction and ultrasonic irradiation / Yuta Nakano ... [et al.] - Nakano, Yuta; Kato, Shigeru; Ito, Takuya; Suganuma, Hideki; Suzuki, Seiichi; Kojima, Toshinori (Universiti Teknologi MARA, Pulau Pinang, 2015)
Trichloroethylene (TCE) is known as one of the persistent pollutants of soil and groundwater. TCE has carcinogenicity and should urgently be decontaminated. In this research, Fenton reaction and ultrasonic (US) irradiation were used for TCE decomposition as low cost and widely targetable advanced oxidation processes. First of all, our previous results related to the TCE decomposition is reviewed. Then the recent results are reported. Reaction temperature was set at 15℃ in order to prevent TCE volatilization. By the ultrasonic irradiation method, it was confirmed that the distribution of the US strength is also most flat inside the reaction vesssel, except the vicinity of the bottom, and TCE was slowly decomposed at constant rate irrespective of the fluctuation of power of the transducer. For the Fenton reaction, TCE-saturated solution (1.0 g/L) added with Fe ion was mixed with hydrogen peroxide solution. The decomposition rate of TCE by the Fenton reaction was measured and compared using both of ferrous ion (Fe2+) and ferric ion (Fe3+). Fairly amount of TCE was immediately decomposed after a reaction start (mixing of solutions) when Fe2+ was used.